Pengembangan Media Pembelajaran Pocket Book Berbasis Pendekatan Saintifik Pada Materi Pengukuran - Badrul Wajdi; Fartina Fartina; Nazipatuzzahrah Nazipatuzzahrah (Kappa Journal, 2024)
This research aims to find out the specifications of the product resulting from development, the feasibility, and effectiveness of the scientific approach-based pocket book learning media on measurement material. This research falls under the category of  research and development (R&D). The method employed in this research was the 4-D method, consisting of the stages of define, design, development, and dissemination. The feasibility level was obtained from the scores given by expert validators and subject teachers, and the 10th-grade students of SPM Ulya Irhamna Bil Qur'an as respondents. The validation from the content expert received a score of 4.13, the validation from the media expert received a score of 4.01, the validation from the subject teacher received a score of 4.09, and student responses yielded a score of 4.18. The research results indicate that the media is suitable for further development. The level of effectiveness was elaborated in the form of pre-test and post-test. The average score obtained from the pretest was 62.5, while the average score obtained from the posttest was 78.9. The categorization of the score based on the N-gain score falls within the range of  0.3 ≤ g ≤ 0.7, categorizing it as moderate effectiveness. Therefore, the interpretation of the N-gain effectiveness score falls within the 40 – 50 percentage range, categorizing it as less effective